BRIDGING THE GAP: THE ROLE OF MICRO-INSURANCE IN A COMPREHENSIVE SOCIALPROTECTION SYSTEM IN SOUTH AFRICA - Letlhokwa George Mpedi; Daleen Millard (Obiter, 2021)
Access to social protection interventions, such as social assistance, social insurance and private insurance, in South Africa is limited. For that reason, plugging the holes in the safety net is undoubtedly one of the most pressing challenges facing South Africa in its quest to design a comprehensive social protection system. The point is that vulnerable persons, just like any other persons, have to contend with social risks (for example, death, poor health, invalidity, etcetera). As a result, similarly to all other persons, they require protection against these risks. It is clear that the current social protection interventions (particularly social insurance, social assistance and private insurance) fail to protect every person in need of such protection adequately in South Africa. Thus, the contribution sets out to investigate the prospects of micro-insurance being used as an instrument to extend social protection coverage to the excluded and marginalized persons in South Africa.